2002
DOI: 10.1111/1468-2370.00075
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of New Product Development: A Review of the Empirical Literature

Abstract: The continuous development and market introduction of new products can be an important determinant of sustained company performance. For approximately 30 years, conceptual and empirical research has been undertaken to identify the critical success factors of new products. This paper reviews the findings of empirical work into the success factors of new product development (NPD). It is the prime objective of this work to summarize the most important findings in a compact and structured way. In addition, shortco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
463
2
57

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(529 citation statements)
references
References 117 publications
(164 reference statements)
7
463
2
57
Order By: Relevance
“…It has also been suggested that green, new product and service development processes appear to extensively involve external stakeholders (Driessen and Hillebrand, 2010). In particular, exploration practices emphasise the early involvement of relevant stakeholders (Polonsky and Ottman, 1998), as doing so generally enables better alignment of the product concept with the requirements of both the customers and the other stakeholders (Ernst, 2002).…”
Section: Sustainability Exploration and Sustainability Exploitation: mentioning
confidence: 99%
“…It has also been suggested that green, new product and service development processes appear to extensively involve external stakeholders (Driessen and Hillebrand, 2010). In particular, exploration practices emphasise the early involvement of relevant stakeholders (Polonsky and Ottman, 1998), as doing so generally enables better alignment of the product concept with the requirements of both the customers and the other stakeholders (Ernst, 2002).…”
Section: Sustainability Exploration and Sustainability Exploitation: mentioning
confidence: 99%
“…Further, the proposed approach allows teams to be dynamically tailored to the design task at hand by providing insight into communication and team interactions. These can then be contrasted with generic characteristics of design teams such as those provided by Ernst (2002) (e.g. multidisciplinary, interfunctional communication, and level of co-operation).…”
Section: Comparison With Extant Approaches and Discussionmentioning
confidence: 99%
“…For example, Robinson (2010) and both emphasized the need to better understand process dynamics of intangible factors in engineering design teams. Similarly, Vuolle et al (2009) (Ernst 2002), subjectivity, and retrospective assessment (Podsakoff et al 2003) in current performance frameworks that do not take a dynamic process view.…”
Section: Dynamic Measurementmentioning
confidence: 99%
“…Atliktų išsamių empirinių tyrimų rezultatai padėjo identifikuoti produkto ar paslaugos inovacijų sėkmę lemiančius veiksnius (Brown, 1998;Heunks, 1998;Holger, 2002;Kleinschmidt, Brentani, Salomo, 2007;Cooper, 2008Cooper, , 2012Zavadskas, 2008;Gammoh, Voss, Skiver, 2011;Strazdas, 2011;ir kt.). Apibendrinus atliktų tyrimų rezultatus, iš esmės galima identifikuoti tuos pačius faktorius, kurie lemia sėkmingą inovatyvios konkurencingos paslaugos ar prekės ekspansiją rinkoje.…”
Section: Vidinę Inovacijų Plėtrą Sąlygojantys Veiksniaiunclassified